Intramuscular midazolam versus intravenous lorazepam for the prehospital treatment of status epilepticus in the pediatric population. (17th January 2015) - Welch, Robert D.; Nicholas, Katherine; Durkalski‐Mauldin, Valerie L.; Lowenstein, Daniel H.; Conwit, Robin; Mahajan, Prashant V.; Lewandowski, Christopher; Silbergleit, Robert; the Neurological Emergencies Treatment Trials (NETT) Network Investigators
Summary Objective To examine the effectiveness of intramuscular (IM) midazolam versus intravenous (IV) lorazepam for the treatment of pediatric patients with status epilepticus (SE) in the prehospital care setting. Methods This multicenter clinical trial randomized patients diagnosed with SE to receive either IM midazolam or IV lorazepam administered by paramedics in the prehospital care setting. Included in this secondary analysis were only patients younger than 18 years of age. Evaluated were the associations of the treatment group (IM vs. IV) with the primary outcome, defined as seizure cessation prior to emergency department (ED) arrival, and with patient characteristics, time to important events, and adverse events. Descriptive statistics and 99% confidence intervals (CIs) were used for the analysis. Results Of 893 primary study subjects, 120 met criteria for this study (60 in each treatment group). There were no differences in important baseline characteristics or seizure etiologies between groups. The primary outcome was met in 41 (68.3%) and 43 (71.7%) of subjects in the IM and IV groups, respectively (risk difference [RD] −3.3%, 99% CI −24.9% to 18.2%). Similar results were noted for those younger than 11 years (RD −1.3%, 99% CI −25.7% to 23.1%). Time from initiating the treatment protocol was shorter for children who received IM midazolam, mainly due to the shorter time to administer the active treatment. Safety profiles were similar. Significance IM midazolam can be rapidly administered and appears to be safe and effective for the management of children with SE treated in the prehospital setting. The results must be interpreted in the context of the secondary analysis design and sample size of the study.